Valerius and Decoratus Crescens on CIL III 15169 - Németh, György (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The paper examines a rediscovered inscription (CIL III 15169) and its dating. It raises the question why the relief depicts one man, though a father and his son were buried under the gravestone.